2019
DOI: 10.3390/nu11051189
|View full text |Cite
|
Sign up to set email alerts
|

Health-Promoting Components in Fermented Foods: An Up-to-Date Systematic Review

Abstract: Fermented foods have long been produced according to knowledge passed down from generation to generation and with no understanding of the potential role of the microorganism(s) involved in the process. However, the scientific and technological revolution in Western countries made fermentation turn from a household to a controlled process suitable for industrial scale production systems intended for the mass marketplace. The aim of this paper is to provide an up-to-date review of the latest studies which invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
146
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 261 publications
(188 citation statements)
references
References 119 publications
(167 reference statements)
5
146
0
8
Order By: Relevance
“…According to several previously published studies, fermented foods have beneficial effects on the gastrointestinal tract system. Moreover, recent studies have shown that supplementation of fermented foods had beneficial effects in improving symptoms of type 2 diabetes mellitus, impaired glucose metabolism, obesity, irritable bowel syndrome, hyperlipidemia, hypertension and osteoporosis [2,3,7,[51][52][53][54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to several previously published studies, fermented foods have beneficial effects on the gastrointestinal tract system. Moreover, recent studies have shown that supplementation of fermented foods had beneficial effects in improving symptoms of type 2 diabetes mellitus, impaired glucose metabolism, obesity, irritable bowel syndrome, hyperlipidemia, hypertension and osteoporosis [2,3,7,[51][52][53][54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…Foods or beverages are fermented through regulation of microbial growth or actions of enzymes [1,2]. Thus, fermented foods are produced depending on factors such as nature of microorganisms, ingredients and environmental conditions [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, microbial resources play a vital role in biotechnology innovation ( Figure 1) and their exploitation in food [68][69][70], industry [71], medicine [72][73][74][75], and the environment [76][77][78] is widely reported in literature. Many papers dealing with the positive effects of fermented food and related microorganisms and compounds have been published, and a comprehensive overview of health-promoting activities and compounds, per raw food matrix and related fermenting microorganisms is reported in the review published by Melini and co-workers [83].…”
Section: Exploitation Of Biological Resources and Connection Between mentioning
confidence: 99%
“…Indeed, it could not only allow the traditional taste of fermented foods to be recovered, but also new, natural fermented food and beverages to be obtained, able to provide health and nutrition benefits and preventing the loss of many species and strains useful for human health [82,83].…”
Section: Exploitation Of Biological Resources and Connection Between mentioning
confidence: 99%
See 1 more Smart Citation